Effect of yeast and acetic fermentation on phytochemical and antioxidant properties of jackfruit pulp (Artocarpus heterophyllus L.) - Aziz Norhazniza, Koh Soo Peng, Mustaffa Razali, Abdullah Rosmawati, Abdul Hamid Nur Syazwani, (Universiti Pendidikan Sultan Idris, 2017)
Effect of yeast and acetic fermentation on phytochemical and antioxidant properties of jackfruit pulp (Artocarpus heterophyllus L.) by Aziz Norhazniza, Koh Soo Peng, Mustaffa Razali, Abdullah Rosmawati, Abdul Hamid Nur Syazwani,